Ruthenium-catalyzed bond cleavage in lignin model compounds containing β–O–4 linkages - Badazhkova, Veronika D.; Savela, Risto; Lassfolk, Robert; Leino, Reko (De Gruyter, 2026)
In this work, the possibility of using ruthenium-based Shvo catalyst for bond cleavage of lignin model compounds and lignin has been investigated. Shvo-catalyzed degradation procedure was applied to four lignin model compounds containing β–O–4 linkages, common for native lignin fractions. The reactions, in general, resulted in Cβ–Cγ and Cγ–Oγ bond cleavage, with the degradation products depending on the exact model compound studied. Distribution of the degradation products can be explained by the range of substituents and structural complexity of the model compounds. The major products of degradation were separated using preparative HPLC and characterized to enable further studies on bond cleavage in lignin. The Shvo-catalyzed degradation protocol was further applied to the lignan hydroxymatairesinol and a model diol with protected primary hydroxyl group. For both compounds, only dehydrogenation of benzylic hydroxyl group in the absence of bond cleavage was observed. With extracted lignin, only thermal degradation of the starting material was evidenced, while detailed characterization of the reaction products was not possible due to their poor solubility and structural complexity.